Company performance improvement: implementation of service culture through human capital in hospitality industry - Rian Andriani; Purwadhi Purwadhi; Disman Disman (Faculty of Economics and Business, Universitas Mulawarman, 2023)
The process of improving service productivity in the hotel industry is of course caused by several fundamentally important factors, including corporate culture and employee human resources factors. A good organizational culture should have the core characteristics of being firmly supported, well-managed, and shared as a whole. Problems commonly faced by employees are related to how to proactively adapt to the company culture so that conflicts do not occur. The research instrument was a questionnaire distributed to 192 hotel employees in West Java, Indonesia. This research aims to conclude whether human capital can mediate the influence of service culture by increasing company performance. The research method used is a simple regression analysis using SPSS and Amos as a calculation tool. The results show that human capital can mediate the influence between service culture and increased company performance in the hotel industry.